Analisis Validitas Perangkat Pembelajaran Kooperatif Tipe STAD Berbantuan Grup Facebook Terhadap Hasil Belajar Siswa - Mursalin, Sri Wahyuni; Odja, Abdul Haris; Nuayi, Abd. Wahidin (Universitas Halu Oleo, 2021)
This study aims to obtain an effective STAD cooperative model physics learning tool to improve high school student learning outcomes on Static Fluid material. This research refers to the Kemp's development model. The results showed that the results of the development of physics learning tools were feasible for use in high school physics learning with the following results: The syllabus got a score of 3.49 (valid), the learning implementation plan got a score of 3.31 (valid), the student teaching materials got a score of 3, 46 (valid), student worksheets get a score of 3.33 (valid).Â Â